A Sampling Load Frequency Control Scheme for Power Systems with Time Delays. (29th June 2022) - Sriraman, R.; Younis, Jihad A.; Lim, C. P.; Hammachukiattikul, P.; Rajchakit, G.; Boonsatit, N.
Abstract : In this study, we investigate the effectiveness of a robust sampled-data H ∞ load frequency control (LFC) scheme for power systems with randomly occurring time-varying delays. By using the input-delay technique, the sampled-data LFC model is reformulated as a continuous time-delay representation. Then, Bernoulli-distributed white noise sequences are used to describe randomly occurring time-varying delays in the sampled-data LFC model. Some less conservative conditions are achieved by utilizing the Lyapunov–Krasovskii functional (LKF) and employing Jensen inequality and reciprocal convex combination lemma to ensure the considered power system has mean-square asymptotic stability under the designed control scheme. The derived results are based on linear matrix inequalities (LMIs) that can readily be solved using the MATLAB LMI toolbox. The criteria obtained are used to analyze the upper bounds for time delays, and a comparison study to validate the efficacy of the presented method is presented.